EFFECTS OF REDUCING THE VOLUME OF THE INTENSITY OF AEROBIC TRAINING ON RESTING HEART RATE IN YOUNG SWIMMERS. (Fiep Bulletin - online, 2011)
Among the benefits of systematically sports for young people are factors related to health, growth, development, psychological well-being and improvement of motor skills. With the increasing participation of children and youth in this involving the systematic training, there is a preoccupation with the applied load and proper recovery. Given this fact, the goal of this study was to investigate the effect of aerobic training, reducing the volume and intensity of training on frequency (HR Rep.) of young swimmers. Twenty swimmers competing (7 females and 13 males) aged between 13 and 14 years were enrolled. For data analysis test was used for statistical analysis for paired samples. The results showed a decrease of 11.63% HR Rep. in both groups and improvement of 11.74% for boys and 11.10% for girls. Thus, this study was presented as a good indicator of cardiovascular adaptation by increasing venous return and stroke volume in young swimmers.
Keywords: swimming; aerobic training and heart rate